Some effects of histamine in the depolarized rat uterus - Blyth, D. I. (1973)
1. The relaxant effect of histamine in the isolated rat uterus remained after the preparation was depolarized in a potassium Ringer. 2. The effect was abolished by the calcium-chelating agent, ethyleneglycol bis-aminoethyl ether-tetraacetic acid (EGTA). 3. Histamine caused relaxation during calcium-induced contractures in a depolarized uterus treated with EGTA, but did not produce relaxation during barium-induced contractures. 4. While responses of a normally polarized rat uterus to acetylcholine were inhibited by histamine, those of a depolarized uterus were enhanced by histamine. The inhibitory effects of isoprenaline and papaverine on acetylcholine responses were maintained in depolarized preparations. 5. Both the enhancing effect of histamine on responses to acetylcholine and the relaxation of calcium-induced contractures were abolished by burimamide, indicating that H(2)-receptors mediate the effects of histamine in the depolarized tissue. 6. A reduction in the rate of exchange of calcium across the depolarized cell membrane was demonstrated with high concentrations of histamine. 7. The results are consistent with the hypothesis that in the rat uterus, the stimulation of H(2)-receptors by histamine is accompanied by a reduction in calcium exchange across the membrane which may result in a decrease in the concentration of free intracellular calcium available to stimulate contraction of the myofilaments. Histamine may act by increasing the binding of calcium within the cell.